Instrument Self-Efficacy for Diabetes Mellitus Type 2 Patients - Silolonga, Wico Neta; Kadar, Kusrini; Sjattar, Elly Lilianty (LPPM STIKES MUHAMMADIYAH GOMBONG, 2019)
Diabetes mellitus (DM) is a disease that can be controlled but, it can cause various complications if the patient unable to manage the disease independently. The ability of a DM patient should be supported by his belief to perform certain behaviors known as self-efficacy. Self-efficacy assessments need to be assess the extent to which DM patients are confident that they can deal with diabetes. Several self-efficacy diabetes assessment instruments have been developed to assess the activity of self-care diabetics. The purpose of this literature study is to identify instruments that can be used to assess the self-efficacy of DM type II patients. Methods: The databases used in this literature review are PubMED, Wiley Online Lybrary, Science Direct, Google Scholar and secondary search. Results: There are 15 articles meet the inclusion criteria. Several research results show the development of DMSES instrument to measure the confidence of DM patients in doing self-care activities of DM patients. DES instrument focuses on patient empowerment and education programs and DSES instrument is a development of self-efficacy assessment of chronic diseases. This instrument can be applied in clinical and research practice but must through an adaptation process according condition and culture of the patient and respondent.